Simplify:
$(3x + 2y) (4x + 3y) - (2x - y) (7x - 3y)$

AcademicMathematicsNCERTClass 8

Given:

$(3x + 2y) (4x + 3y) - (2x - y) (7x - 3y)$

To do:

We have to simplify the given expression.

Solution:

$(3x + 2y) (4x + 3y) - (2x - y) (7x - 3y)=[3x (4x + 3y) + 2y (4x + 3y)]-[2x (7x-3y)-y(7x-3y)]$

$= (12x^2 + 9xy + 8xy + 6y^2) - (14x^2 - 6xy - 7xy + 3y^2)$

$= (12x^2 + 17xy + 6y^2) - (14x^2 - 13xy + 3y^2)$

$= 12x^2 + 17xy + 6y^2 - 14x^2 + 13xy - 3y^2$

$= 12x^2 - 14x^2 + 17xy + 13xy + 6y^2 - 3y^2$

$= -2x^2 + 30xy + 3y^2$

$= -2x^2 + 3y^2 + 30xy$

raja
Updated on 10-Oct-2022 13:19:30

Advertisements